2018
DOI: 10.1200/jco.2017.75.5165
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic Model for Stratification of Radioresistant Nasopharynx Carcinoma to Curative Salvage Radiotherapy

Abstract: Purpose To investigate for a prognostic index (PI) to personalize recommendations for salvage intensity-modulated radiotherapy (IMRT) in patients with locally recurrent nasopharyngeal carcinoma (lrNPC). Methods Patients with lrNPC from two academic institutions (Sun Yat-Sen University Cancer Center [SYSUCC-A; n = 251 (training cohort)] and National Cancer Centre Singapore [NCCS; n = 114] and SYSUCC-B [n = 193 (validation cohorts)]) underwent salvage treatment with IMRT from 2001 to 2015. Primary and secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
82
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 28 publications
7
82
0
Order By: Relevance
“…While small volume disease might benefit with slightly higher dose than 60 Gy 10 (EQD2) as shown in the multi‐dimensional logistic model, the local control rate is estimated to be less than 50% if the GTV exceeds 20 cc, and it falls rapidly to less 10% irrespective of radiation dose if the GTV exceeds 80 cc. This detrimental effect of increasing GTV volume has been consistently reported in other series . Specifically, GTV volume exceeding 30 cc and 38 cc were found to be the negative prognostic factor in the study by Tian et al and Han et al, respectively.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…While small volume disease might benefit with slightly higher dose than 60 Gy 10 (EQD2) as shown in the multi‐dimensional logistic model, the local control rate is estimated to be less than 50% if the GTV exceeds 20 cc, and it falls rapidly to less 10% irrespective of radiation dose if the GTV exceeds 80 cc. This detrimental effect of increasing GTV volume has been consistently reported in other series . Specifically, GTV volume exceeding 30 cc and 38 cc were found to be the negative prognostic factor in the study by Tian et al and Han et al, respectively.…”
Section: Discussionsupporting
confidence: 70%
“…Higher rates of treatment related fatal complications were observed in studies that reported treatments with planned RT doses larger than 60 Gy. High re‐irradiation dose (above 68‐70 Gy) and large recurrent gross tumor volume were shown to associate with poor treatment outcomes . It is evident that local control benefited from dose escalation could be potentially offset by the detrimental effect of life‐threatening late toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…Various prognostic models have been proposed aiming to identify patients who might best benefit from the use of re-RT. [10][11][12] Our analysis suggests that age and rGTV volume were the most important parameters for OS. However, in a case-matched retrospective study, similar survival outcomes were observed for patients who received re-RT vs chemotherapy alone, 22 and the latter was inevitably associated with fewer RT-related toxicities.…”
Section: Discussionmentioning
confidence: 73%
“…Analyses of survival outcome and prognostic factors were performed by using the Kaplan-Meier method, log-rank test, and Cox proportional hazard model. Prognostic factors based on prior literature findings [9][10][11][12] including age, gender, time from primary diagnosis to recurrence, rT status, presence of concomitant nodal metastasis, and treatment modalities were considered, with backward elimination used to determine the significant factors. Among the re-RT group, other prognostic factors such as recurrent tumor volume, radiation dose, and concomitant chemotherapy were also analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in our study, the outcomes of univariate analysis may be less convincing on account of the unbalanced distribution of recurrent tumor stage and treatment protocols, while there are no exactly standard therapeutic modalities in patients with lrNPC. With the developed surgical technology, nasopharyngectomy is recommended for early stage resectable disease . Comparing the efficacy of surgery with re‐irradiation is difficult as patients eligible for surgery generally have earlier stage disease (usually rT1‐2), smaller tumor volume and fewer comorbidities.…”
Section: Discussionmentioning
confidence: 99%